Solving eventual bonding quality to enhance adhesion for QFN packages - Suresh, Kumar; Subramonian, Sivarao; Cheong MT; Mohd Azmeer; Harun, Fuaida (IEEE, 2010)
Many of the components used extensively in today's handheld market are beginning to migrate from traditional lead frame design to lead less or non leaded. The primary driver for handheld manufacturers is the saved PC board space created by these components' smaller mounting areas. In addition, most components also have reductions in weight and height, as well as an improved electrical performance. As critical chip scale packages are converted to non- leaded designs, the additional space saved can be allocated to new components for added device functionality Similar to leaded components, non leaded designs use wire bond as the primary interconnection between the IC and the frame. However, due to the unique land site geometry and form factor density, traditional wire bond processes may not produce high yielding production. For these designs, additional wire bond capabilities and alternate processes are needed to produce acceptable production yields. This paper discusses the eventual challenges of wire bond for QFN package designs and describes how new wire bond capabilities and process optimization can improve production yields but on top of the impact need to be consider as well during the higher force impact which could deteriorate the looping profile on the adjacent wire. The advantages of the conversion of the design which could improve the conversion rate on the production.